A 31-year review of composite radial forearm free flaps for head and neck reconstruction. Issue 7 (September 2022) - O'Connell, J.E.; Koumoullis, H.; Lowe, D.; Rogers, S.N.
Abstract: The aim of this study was to report the patient characteristics and radial fracture rates in a consecutive series of composite radial forearm free flap (CRFFF) for head and neck reconstruction over a 31-year period. The patients were identified from between 1990 to 2020 inclusive from theatre records and records from previous analyses at the Unit on free flap outcomes. Electronic case notes were accessed where available, to gather information on the operation, histopathology, and radiographs. Patients were categorised into three groups for analysis: (1) new oral cancers with a composite radial being the first choice of flap, (2) new oral cancers with a composite radial being the choice of flap following compromise of another bony flap, (3) osteoradionecrosis (ORN) cases. There were 103 CRFFF cases, median (IQR) age 69 (59-80) years, comprising 78 (Group 1), 5 (Group 2) and 20 (Group 3). The CRFFF failure rate was 6% (6/103) and the radius fracture rate was also 6% (6/103), both with 95% confidence interval 2.2-12.2%. Of the 6 radius fractures, 1 underwent surgical management (rush nailing), 1 died in hospital and the others managed with cast immobilisation. Two-year overall survival after surgery for the103 patients was 54% (SE 5%), while 5-year survival was 40% (SE 5%). In conclusion, in spite of the familiarity with other bone flaps such as fibular free flap, DCIA, scapula, and the limited bone stock and potential fracture related morbidity associated with the CRFFF, this flap still has a place in the surgical reconstructive armamentarium.